Determinants of sustainable software practices in the Malaysian electronic industry and the role of knowledge accessibility - Chukwuyem, Giweze (2023)
The issues of software sustainability are considered a general focus for experts and an emerging area nowadays in contemporary research in the electronic industry. This current study focuses on the determinants of sustainable software practices in the Malaysian electronic industry (i.e., electronic components, consumer electronics, and industrial electronics), and attempts to investigate the possibilities of decreasing unsustainable activities. Emerging studies have not consolidated software sustainability in the electronic industry, thus suggesting a knowledge gap in the existing literature. The developers have not integrated the aspects that support environmental performance from the industrial sector. Therefore, the current study investigates the determinants of sustainable software practices in the Malaysian electronic industry. The research objective was conceptualised and a framework was developed which supports the GREENSOFT Reference Model. The research applied a quantitative approach. Data was received through questionnaire distribution among 250 employees from different software departments in the electronic industry. The study applied Structural Equation Modelling (SEM) using SmartPLSv3.0 to process the data. The findings show that software governance, software strategy, software practitioners, sustainable environmental practices and knowledge accessibility positively influence sustainable software practices. The path coefficient results reveal that knowledge accessibility has the strongest influence, followed by software strategy. In addition, the moderating result shows that knowledge accessibility moderates the relationship between software strategy and sustainable software practices. While others (i.e., software governance, software practitioners, and sustainable environmental practices) show no moderating effects. Therefore, the results from the study provide some insightful contributions for policymakers to pursue green practices and also help in the implementation and value accessibility of software sustenance for social, economic and environmental performance in the Malaysian electronic industry.